Venturia Crataegi Causing Scab On Crataegus Songarica: Morpho Molecular Charcterization And A New Record From India (Applied Biological Research, 2019)
A field survey was conducted in the years 2017 to 2019 for the collection of  diseased samples of various crops including Crataegusspecies, from Pulwama  and Srinagar districts of Jammu and Kashmir. The leaf and fruit samples of  Crataegus songarica showing scab symptoms were collected and brought to  the laboratory. During disease monitoring it was noticed that the disease  initiated as dark spots on leaves and fruits; and then often covered the entire  surface. The mycelium on host was septate, immersed, subcuticular and pale  olivaceous; hyphae branched and 2-4 µm wide.On MEA medium the  mycelium was septate, branched, interwoven, light pale to olivaceous brown and 3-5 µm wide. The conidia were solitary, fusiform to obclavate having 0- 1 septum (avg. size; 15.64 × 5.76 µm). Based on morphocultural  characteristics the fungus was identified as Venturia crataegi. The identity  was confirmed by sequencing of ITS region of the pathogen using ITS1 and  ITS4 primer. The ITS sequence was submitted to Genbank of NCBI under  Accession No. MK478372. For phylogenetic analysis, the sequence was compared with other sequences of Venturia species available at NCBI which  showed close relatedness of the present sequence with V. crataegi (Accession  No. MH855705.1). The present study forms the first report of crataegus scab  caused by Venturia crataegi from India.
Keywords: Crataegus sonarica; phylogenetics; rDNA-ITS; scab; Venturia crataegi